Was Clarke a Voluntarist? - Lukas Wolf (Journal of Modern Philosophy)
The distinction between voluntarism and intellectualism has recently been criticized for inaccurately characterising early modern theories of divine freedom. In response, defenders of the distinction have argued that these labels are needed in order to account for the famous correspondence between Leibniz (intellectualist) and Clarke (voluntarist). In this paper, I argue that the voluntarism/intellectualism distinction is unable to account for the opposition between Leibniz and Clarke. In the first part, I provide an analysis of Clarke’s theory of divine freedom, and show how he employs the distinction between activity and passivity in order to account for the separation between God’s will and intellect, which ultimately safeguards God’s freedom. I also analyse Clarke’s correspondence with Leibniz, and show how Clarke deals with choice among equals, the principle of sufficient reason, and the principle of the best. In the second part, I argue on the basis of this analysis that Clarke is not a voluntarist, but should instead be interpreted as an intellectualist (if one wants to keep the labels). Therefore, the Leibniz-Clarke correspondence cannot be explained as a clash between voluntarism and intellectualism.